Identifikasi Tingkat Kemiripan Dokumen Teks Menggunakan Fungsi Hash Pada Algoritma Winnowing Dan Pattern Recognation Pada Algoritma Ratfliff/Obershelp - Abdul Halim Hasugian; Yusuf Karim Rambe; Muhammad Siddik Hasibuan (LPPM Universitas Al Washliyah Labuhanbatu, 2023)
The development of this very advanced technology in computers era, all document have turned into softcopy file, which can be accessed with computer or smartphone. So many people commit plagiarism by not listed the source and resulting copyright infringement. The plagiarism can be interpreted as an action that takes statements of theft other people’s ideas. In law, patents and intellectual property rights are already regulated In law. Therefore to make it easier for teachers and lecturers in academic. Identification of document is needed to know whether the document includes plagiarism by detecting the similarity of text between documents. Then the authenticity in each document can be maintained its authenticity. The process of identification are using Winnowing and Ratcliff/Obershelp algorithm. Winnowing algorithm is algorithm used to perform the process of checking word similarity (document fingerprint) to identify plagiarism of document. Ratcliff/Obershelp is also used to detect similarities, but it works by returning value that can be userd as a percentage to show the similarity of two strings by calculating the number of characters contained in two strings. Both of these algorithm can be used to identify percentage of similarity of text document.